The causal effect of age at migration on youth educational attainment - Dominique Lemmermann; Regina T. Riphahn (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2016)
We investigate the causal effect of age at migration on subsequent educational attainment in the destination country. To identify the causal effect we compare the educational attainment of siblings at age 21, exploiting the fact that they typically migrate at different ages within a given family. We consider several education outcomes conditional on family fixed effects. We take advantage of long running and detailed data from the German Socio-Economic Panel, which entails an oversample of immigrants and provides information on language skills. We find significant effects of age at migration on educational attainment and a critical age of migration around age 6. The educational attainment of female immigrants responds more strongly to a high age at immigration than that of males.
Keywords: I21; J61; C21; 330; immigration; education; integration; school attainment; Germany; causal estimation; family fixed effect